Neural networks with radial basis applied to the improve of quality - Cevallos Ampuero, Juan (2008)
This research has led to construct an artificial neural network ARN with Radial Basis Function, and using Mahalanobis distance RND, for improving the quality of process design, which have performed better than those obtained with the for traditional statistical analysis of design of experiments and other RNA that already exist, for cases that are working with several independent and dependent variables in which its relations are not linear. It also allows with the RND obtain input parameters to achieve a desired level of quality, for it applies a methodology that uses RNAReverse and Direct at once.